2020
DOI: 10.1016/j.eucr.2020.101345
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal emphysema with characteristics of Fournier's gangrene in a community setting

Abstract: Fournier's gangrene is a life-threatening type of necrotizing fasciitis associated with a high rate of morbidity and mortality. The patient is a 29-year-old incarcerated male who presented to the ED with left-sided scrotal crepitus extending into the axilla and testicular swelling. The patient endorsed a pimple on his left scrotum accompanied with groin pain. He had a prior history of foreign body removal and self-mutilating behaviors. The patient was taken for surgical exploration out of concern due to a subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In addition to comorbidities, accompanying diseases have also taken their place in the etiology of Fournier gangrene. Unalp et al, found in their study that anorectal abscess and primary scrotal abscess accompany Fournier gangrene (11). In a case report reported by Cook et al, epididymal cysts were found to be present along with epididymis (12).…”
Section: Discussionmentioning
confidence: 93%
“…In addition to comorbidities, accompanying diseases have also taken their place in the etiology of Fournier gangrene. Unalp et al, found in their study that anorectal abscess and primary scrotal abscess accompany Fournier gangrene (11). In a case report reported by Cook et al, epididymal cysts were found to be present along with epididymis (12).…”
Section: Discussionmentioning
confidence: 93%
“…The first one derives from the scrotum itself. This mechanism includes either self mutilation/injury of the scrotum where the air entry is direct [6] or infectious processes such as in perinephric abscess or Fouriner's gangrene that often presents with scrotal emphysema and leads to disruption of the scrotal skin allowing the entrance of microorganisms and air production within the scrotum [7].…”
Section: Pathophysiologymentioning
confidence: 99%